Effects of Dextran on the Molecular Structure and Tensile Behaviour of Human Fibrin - Dhall, T. Z; Bryce, W. A. J; Dhall, D. P (Thrombosis and Haemostasis, 1976)
Characteristic changes induced by dextran during the conversion of fibrinogen to fibrin have previously been shown to be associated with profound alterations in morphology of fibrin. However, whether dextran is incorporated into the fibrin molecule and whether morphological changes are associated with alterations in mechanical behaviour of formed fibrin was unclear. The investigations described show that the fibrin made in the presence of dextran has a shortened syneresis time, a lowered modulus of elasticity, an increased elongation and diminished ultimate strength at break. The molecular composition of fibrin clots remains unaltered despite the altered mechanical properties and morphological changes. Furthermore, dextran is not incorporated into the fibrin structure in any appreciable quantity. It is suggested that these several effects of dextran on clot morphology, tensile behaviour and kinetics of fibrin formation arise from increased forces of attraction between fibrin molecules such that fibrin chains are held together by weak secondary cross-links rather than by stronger primary cross-links which are hidden within the thicker fibrin chain bundles.Recently Muzaffar et al. (1972 a, c) showed that the addition of small amounts of dextran in vitro to purified fibrinogen solution as well as platelet – poor plasma induces characteristic alterations in the kinetics of fibrin formation on account of accelerated polymerization of fibrin monomer. Further, fibrin made under such conditions was found to differ morphologically from control fibrin (Muzaffar et al. 1972 b) and to show an increased coarseness of individual fibrin fibre on electron microscopy together with an associated looseness of fibrin mesh. The degree of abnormality in fibrin morphology was found to be determined by the final dextran concentration. More significantly, dextran was demonstrated to induce similar changes in the kinetics of fibrin formation as well as in fibrin morphology of clots made from plasma after the infusion of clinical dextran fractions in pharmacological dosage in man. However, it is not clear whether dextran-induced structural alterations in fibrin are indicative ofbasic differences in its molecular composition nor whether these changes are associated with alterations in the mechanical strength of fibrin. Clearly these are fundamental questions with respect to the pharmacological effects of dextran in relationship to its clinically well documented antithrombotic activity (Lambie et al. 1970). We have investigated both these questions and report here our principal findings.